Writing amidst the Scribbles: The Role and Place of Writing in Ancient Maya Graffiti - Christophe Helmke; Jarosław Źrałka (Papers from the Institute of Archaeology, 2021)
<!–[if gte mso 9]> Normal 0 false false false EN-GB X-NONE X-NONE <![endif]–><!–[if gte mso 9]> <![endif]–><!–[if gte mso 10]> <![endif]–>The significant corpus of ancient Maya graffiti (c. 200 BC-AD 950) attests to the widespread practice of secondarily altering architectural surfaces during the course of their use. For the most part this corpus is highly figurative and includes a series of schematic elements that attest to their production by the hands of a variety of agents. As one of the largest corpora of graffiti from any early civilization, the figural representations include a wide array of themes. Some graffiti feature complex, narrative scenes that document important moments of ritual life of the ancient Maya. Almost paradoxically, amid the intricate and highly figurative scenes are hieroglyphic graffiti. What do these written graffiti record, and what is the degree of literacy that these attest to? This raises a series of interesting questions including whether written and figural graffiti were etched onto walls by the same individuals, or whether these represent different social segments each leaving their mark. From these observations follow a series of important ramifications as to authorship, the use of the built environment as well as the motivations behind the graffiti itself.
Keywords: Ancient Maya; Graffiti; Hieroglyphic Writing